2006
DOI: 10.1111/j.1530-0277.2006.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of FASD in a Province in Italy: Prevalence and Characteristics of Children in a Random Sample of Schools

Abstract: Using careful measures of ascertainment in a primary school setting, these results provide relatively high estimates of the prevalence of FASD and raise the question of whether FASD is more common in the western world than previously estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
136
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 31 publications
6
136
2
6
Order By: Relevance
“…[56][57][58][59][60][61] Recruitment of mothers to obtain maternal risk data posed significant challenges for the interviewers. Therefore, variables that differentiate maternal risk in this population were not as evident or readily obtained in this US population or in our Italian studies 15,16 as elsewhere. [23][24][25] Individualized risk for FASD via genetic and epigenetic factors may be more important to explore in this and similar middle and upper SES populations than the more generalized lower SES and childbearing risk factors of higher prevalence populations.…”
Section: Maternal Risk Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…[56][57][58][59][60][61] Recruitment of mothers to obtain maternal risk data posed significant challenges for the interviewers. Therefore, variables that differentiate maternal risk in this population were not as evident or readily obtained in this US population or in our Italian studies 15,16 as elsewhere. [23][24][25] Individualized risk for FASD via genetic and epigenetic factors may be more important to explore in this and similar middle and upper SES populations than the more generalized lower SES and childbearing risk factors of higher prevalence populations.…”
Section: Maternal Risk Measurementsmentioning
confidence: 99%
“…Not only the cardinal facial features, but other facial measurements and minor anomalies are also important discriminators of FASD. Based on this study and other population-based studies, [10][11][12][13]15,16 other minor anomalies, such as those shown in Table 2, are reflected in the total dysmorphology score, which differentiates well the FASD diagnostic groups. Minor anomalies play an important role in identifying affected children.…”
Section: Physical Characteristics Of the Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…The active case ascertainment method has been employed in epidemiological studies of FASD conducted in the USA [11] and a number of other countries, including South Africa [32], Italy [38], and Croatia [39]. Unlike the surveillance method described above, the active case ascertainment approach has targeted all potential participants in a given population.…”
Section: The Active Case Ascertainment Methodsmentioning
confidence: 99%
“…In Italy, the prevalence of FAS is 3.7-7.4/1,000 births (May et al, 2006). However, in developing countries, such as South Africa, the numbers are very high, and the rate varies between 68 and 89.2/1,000 births (May et al, 2007).…”
mentioning
confidence: 99%